Os pequenos produtores de leite de Angatuba/SP: alguns apontamentos - Ferrari, Laura Lisboa (Universidade Federal de São Carlos, 2023)
The dairy activity in Brazil has an important social and economic role, it corresponds to the sourceof income of countless farmers, including family members. In 2017, the publication of the PaulistaDairy Beef Development Plan disclosed the significant reduction of milk producers in the country,indicating a more competitive scenario that would select the most technical and productive. In thiscontext, we propose to study the small milk producers in the Municipality of Angatuba, located inthe Southwest of São Paulo. This study aims to analyze the profile of these producers, the socioeconomic conditions and their production conditions, identifying from the information obtained, the difficulties and challenges faced. Against the trend of the state of São Paulo, when analyzing the data from the municipality of Angatuba, we realize that what happened was an increase in cattle farming. We then formulated the following question to support the analyses: whyin Angatuba did not occur the reduction of the area with cattle raising? What explains this phenomenon? Could we associate it with the specific characteristic of local production? What would be this characteristic found in small producers? To achieve the objectives of the study, the research included a bibliographical research and an empirical research characterized as exploratory,descriptive and interpretive. Interviews were carried out with 15 milk producers in the municipality, carried out through google forms, sent via WhatsApp, phone calls and in person, considered family farmer. It can be said that, for the producers who participated in the research, the main difficulties for the strengthening and permanence in the dairy activity are related to the lack of incentive for the dairy activity, instability of the price paid per liter of milk and the high cost of the inputs.
The small milk producers of Angatuba/SP: some notes
Keywords: Bovinocultura leiteira; Agricultura familiar; Produtor de leite; Dairy cattle; Family farming; Milk producer; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA